Research and Development of Comprehensive Performance Test Bench for RV Reducer of Robot - Wang Ruixin; Liu Hongqi; Zhang Jingcai; Gong Yu; Wu Zhe (Jixie chuandong)
Aiming at the test detection of the performance and accuracy of RV reducer,a comprehensive performance test bench,which can complete the detection of transmission accuracy,torsional stiffness,backlash,friction torque and no-load start stop torque is developed. The test bench based on optical,mechanical,electrical and other advanced measurement technology,the grating high frequency subdivision,precision assembly and error compensation and other proprietary technology are proposed,the 1″high-precision measurement and multi-performance integrated measurement and the serialization are realized. Through user verification,the bench fully meets the requirements of engineering test.